The financial performance determinants of the largest banks in Kazakhstan - Yespergenova, L.; Zhakusheva, Zh.; Faizulayev, A. (Journal of Economic Research & Business Administration, 2023)
The banking industry plays a significant role in the development of the economic growth of the country. The purpose of this study is to determine the key factors that influence the profitability of the banking industry in Kazakhstan from 2012 to 2020 using firm-specific and macroeconomic variables. For this research, 8 banks and 9 years were selected and the data were analyzed according to the feasible generalized least squares (FGLS) method. Findings demonstrate that political stability, liquidity risk, and interest rate have negative, and GDP growth, inflation, and NPL have a positive, but insignificant impact on profitability. Capital adequacy and bank size resulted in a positive and significant effect on ROA. As a recommendation, the banks should emphasize TETA and size to be profitable. To the best of our knowledge, this paper contributes to the existing literature is twofold. First of all, it is the first study that conducted empirical analysis on the 8 largest banks of Kazakhstan by employing the FGLS method determining the financial performance. Secondly, the number of variables and years were broadened compared to previous researchers and a political stability indicator was added to the study. The practical significance of this paper recommends to policymakers, managers, and government officials should pay more attention to internal factors rather than external factors, because the expansion of the size of banks will improve the financial performance of banks, and eventually, this will be incorporated to into the development of the financial market of the country. Keywords: profitability; largest banks; economic growth; political stability.